A Quick-Look Method for Initial Evaluation of Gas Hydrate Stability below Subaqueous Permafrost - Umberta Tinivella; Michela Giustiniani; Héctor Marín-Moreno (Geosciences, 2019)
Many studies demonstrated the coexistence of subaqueous permafrost and gas hydrate. Subaqueous permafrost could be a factor affecting the formation/dissociation of gas hydrate. Here, we propose a simple empirical approach that allows estimating the steady-state conditions for gas hydrate stability in the presence of subaqueous permafrost. This approach was derived for pressure, temperature, and salinity conditions typical of subaqueous permafrost in marine (brine) and lacustrine (freshwater) environments.